Risk and outcome of non‐Hodgkin lymphoma among classical Hodgkin lymphoma survivors. Issue 18 (24th June 2013) - Xavier, Ana C.; Armeson, Kent E.; Hill, Elizabeth G.; Costa, Luciano J.
Abstract : BACKGROUND: Survivors of classical Hodgkin lymphoma (cHL) are at an increased risk of developing secondary non‐Hodgkin lymphomas (sNHLs). To the authors' knowledge, the outcome of patients with sNHL compared with their de novo counterparts (dnNHL) is unknown. METHODS: Data from 26, 826 cases of HL from the Surveillance, Epidemiology, and End Results (SEER) program that were diagnosed between 1992 and 2009 were used to obtain the risk of further development of different subtypes of sNHL. The survival of patients with sNHL was compared with that of matched patients with dnNHL. RESULTS: The estimated cumulative incidence of sNHL was 2.50% (95% confidence interval [95% CI], 2.10‐2.89) at 15 years from the diagnosis of cHL. The standardized incidence ratio was 10.5 (95% CI, 8.9‐12.4) for aggressive B‐cell NHL, 4.0 (95% CI, 3.1‐5.1) for indolent B‐cell NHL, and 14.6 (95% CI, 10.3‐20.1) for T‐cell NHL. Patients with indolent B‐cell sNHL had a worse overall survival compared with their dnNHL counterparts (hazards ratio [HR] of death, 2.7; 95% CI, 1.3‐5.7). Survival was not significantly different between patients with sNHL and those with dnNHL with regard to aggressive B‐cell NHL (HR, 1.3; 95% CI, 0.6‐2.7) or T‐cell NHL (HR, 0.8; 95% CI, 0.3‐1.8). CONCLUSIONS: The risk of developing sNHL after cHL is substantial. Although patients with indolent B‐cell sNHL have inferior survival, patients with aggressive B‐cell sNHL and T‐cell sNHL have survival comparable to that of their de novo counterparts. Cancer 2013;119:3385–92 . © 2013 American Cancer Society . Abstract : Survivors of classical Hodgkin lymphoma are at 7.5‐fold higher risk of developing non‐Hodgkin lymphoma of various histologies than the general population, Survivors who develop T‐cell and aggressive B‐cell non‐Hodgkin lymphoma appear to have survival that is similar to that of their de novo counterparts.